Evaluation of the electronic self-report Symptom Screening in Pediatrics Tool (SSPedi). Issue 1 (1st November 2016) - O'Sullivan, Cathy; Lee Dupuis, L; Gibson, Paul; Johnston, Donna L; Baggott, Christina; Portwine, Carol; Spiegler, Brenda; Kuczynski, Susan; Tomlinson, Deborah; Tomlinson, George A; Sung, Lillian
Abstract : Objective: We previously developed the paper-based Symptom Screening in Pediatrics Tool (SSPedi) designed for paediatric cancer symptom screening. Objectives were to evaluate and refine the electronic mobile application (app) of SSPedi using the opinions of children with cancer. Methods: Participants were children 8–18 years of age with cancer. Participants completed electronic SSPedi on their own and then responded to semistructured questions to determine whether they found electronic SSPedi easy or difficult to complete and understand, understood and liked the app features (audio and animation), and understood previously difficult to understand concepts with the introduction of a help menu. After each group of 10 children, responses were reviewed to determine whether modifications were required. Results: 20 children evaluated electronic SSPedi. None found electronic SSPedi difficult to complete or understand. All children understood the app features and each of the 4 more difficult to understand concepts after using the help menu. 19 of 20 children thought the app was a good way to communicate with doctors and nurses. Conclusions: We finalised an electronic version of SSPedi that is easy to use and understand with features specifically designed to facilitate child self-report. Future work will evaluate the psychometric properties of electronic SSPedi.